ChemInform Abstract: Fast and Highly Chemoselective Alkynylation of Thiols with Hypervalent Iodine Reagents Enabled Through a Low Energy Barrier Concerted Mechanism. Issue 22 (15th May 2015) - Frei, Reto; Wodrich, Matthew D.; Hari, Durga Prasad; Borin, Pierre‐Antoine; Chauvier, Clement; Waser, Jerome
Abstract: The reaction tolerates alkyl and aryl ethynyl substituted benziodoxolone reagents equipped with various functional groups.